Identitas Ekologis dan Representasi Sosial UMKM Hijau: Nilai Ergo-Ikonik, Performativitas, dan Resistensi Representasi dalam Ekonomi Platform - Andriyansah Andriyansah (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
Amid growing market demands for sustainability, several green micro, small, and medium enterprises (MSMEs) in Indonesia have begun to construct ecological identities through digital media as a strategy for value differentiation. However, these representational practices go beyond mere commercial promotion. They reflect a complex interplay between local values, global consumer expectations, and the algorithmic logic embedded within digital platforms. This study investigates how green MSME actors construct, negotiate, and perform social representations of sustainability in digital spaces. Employing an interpretive qualitative approach, the study adopts a multi-sited case study design. It uses visual-narrative analysis to examine digital campaign content from MSMEs engaged in plastic recycling, ecoprint textile production, and natural honey harvesting. Data were collected through online observation, digital document analysis, and limited narrative interviews, and analyzed through the theoretical lenses of social representation, ecological identity, performativity, and platform economy. The findings reveal three dominant patterns: (1) the symbolization of ergo-iconic value, combining tangible ecological practices with aesthetic visualizations as symbolic capital; (2) performative and algorithm-driven sustainability, where content is crafted to attract visibility within a competitive platform ecosystem; and (3) representational resistance, where certain MSMEs choose to highlight complex ecological processes that may not be “Instagrammable” but are instead educational and contextually grounded. The study concludes that the ecological identities of green MSMEs in Indonesia are shaped through representational labor that is symbolic, relational, and conditioned by structural asymmetries within the digital economy. These findings contribute to the fields of environmental communication, digital moral economies, and sustainability strategies in the context of the Global South.